The study on entrepreneurial education in the university through stakeholder involvement - Lilia COVAȘ; Angela SOLCAN (Eastern European Journal of Regional Studies, 2018)
This article reports on a study concerning the entrepreneurial potential in the Academy of Economic Studies of Moldova and identifying the peculiarities, being analysed from the stakeholders’ perspective. The research was carried out within the project ReSTART - Reinforce entrepreneurial and digital skills of students and teachers to enhance the modernization of higher education in Moldova, funded by Erasmus+ program. Since entrepreneurship education is about developing the ability to act in an entrepreneurial manner, attitudes and behaviors are perhaps more important than the knowledge and skills concerned in running a business. Stakeholders can and should play an important role in tailoring university entrepreneurial strategies and actions and supporting their implementation. This can be done through building stakeholder engagement – with stakeholders as partners in the design, planning, implementing and evaluating of entrepreneurship education policy and activity at all levels. The conclusion of this paper redefine the analysis of local target groups’ satisfaction related to entrepreneurial and digital skills, by integrating the needs of all university stakeholders (students, teachers, enterprises, professional association, public institutions and noncommercial organizations).